Analisis bottleneck pada proses ganti meter baru di gudang PDAM Surya Sembada Surabaya dengan metode Root Cause Analysis - Aditya, Bintang Anggry Awan Putra; Winursito, Yekti Condro (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research aims to provide an in-depth understanding of the causes of bottlenecks in the water meter replacement process at PDAM Surya Sembada Surabaya and offer better solutions to overcome them. This field research was conducted at PDAM Surya Sembada Surabaya using data collection methods such as observation and direct interviews with managers or relevant task force members. The collected data was then analysis using Root Cause Analysis (RCA) technique.  The findings of this study show that there are two main obstacles in the work: the water meter procurement process that uses a tender system that requires a long delivery time, and the lack of flexibility in project scheduling related to weather conditions, coupled with tight targets and pressure to complete tasks. Therefore, improvements are needed in the water meter procurement process and policies regarding target adjustments in times of adverse weather conditions.